'Every Hungarian of any value to intelligence': Tibor Eckhardt, John Grombach, and the Pond. Issue 5 (28th July 2016) - Stout, Mark; Kádár Lynn, Katalin
Abstract: Tibor Eckhardt, a Hungarian émigré, was a key player in American intelligence operations regarding Hungary during World War II and the early Cold War. He worked closely with a secretive American intelligence organization headed by John Grombach, an American intelligence officer who was a vehement opponent of the CIA. Though Eckhardt and Grombach shared concerns about the CIA, they were also forced to cooperate with it. Eckhardt's endeavors and those of the many Hungarians whose intelligence work he coordinated were ultimately futile. Hence, they were representative of the efforts of freedom-loving Hungarians to liberate their country during the Cold War.